2016
DOI: 10.14434/vad.v2i0.27941
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for Collecting Human Cardiac Tissue for Research

Abstract: This manuscript describes a protocol at the University of Kentucky that allows a translational research team to collect human myocardium that can be used for biological research. We have gained a great deal of practical experience since we started this protocol in 2008, and we hope that other groups might be able to learn from our endeavors. To date, we have procured ~4000 samples from ~230 patients. The tissue that we collect comes from organ donors and from patients who are receiving a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Figure 5A shows representative records measured for a LV preparation isolated from an organ donor. Consistent with previous results from human myocardium ( 15 ), force overshot the steady-state isometric value during the recovery phase ( 20 , 21 ). The k tr values increased approximately linearly with steady-state isometric force in every experimental group ( Figure 5B ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Figure 5A shows representative records measured for a LV preparation isolated from an organ donor. Consistent with previous results from human myocardium ( 15 ), force overshot the steady-state isometric value during the recovery phase ( 20 , 21 ). The k tr values increased approximately linearly with steady-state isometric force in every experimental group ( Figure 5B ).…”
Section: Resultssupporting
confidence: 92%
“…Previous data from the laboratory ( 15 ) showed that heart failure had a greater impact on the contractile properties of the middle transmural region of the LV than on samples from the sub-epicardium or sub-endocardium. This study compared samples from the RV and the LV mid-myocardium to optimize the probability of detecting important effects.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations